Pembunuhan Anak oleh Ibu Kandung yang di Bawah Umur - Putu Ayu Devi Laxsmi; I Ketut Sukadana; I Nyoman Sujana (Jurnal Preferensi Hukum, 2021)
A phenomenon of the occurrence of criminal acts committed by children with various and various cases and characteristics that have not been able to account for their actions legally, which in Law Number 11 of 2012 concerning the Juvenile Justice System, is intended to provide protection and protection for children in to welcome his long-term future, but besides children as victims of criminal acts, it is possible for children to be criminals. Therefore, how is the judge's judgment in imposing a criminal sentence on a child who commits a criminal act of murder in Decision Number: 18/Pid.Sus.Anak/2016/PN. Dps? And what is the criminal sanction imposed by the judge on the perpetrator of the crime of murder the Number: 18 /Pid.Sus.Anak/2016/PN. Dps. In this study the author uses the Normative research method through his study of literature studies, while the problem approach in this study uses a legislative approach that analyzes legislation and uses a conceptual approach that analyzes problems with legal concepts from books and literature and approaches the case. The results of this study are Judges in considering criminal cases Number: 18/Pid.Sus.Anak /2016/PN. DPS, which is carried out by children because the perpetrators of criminal offenses are still underage, and have never committed an unlawful act before and promised not to repeat other violations of law. And Based on the case of killing a child as referred to in case Number: 18/Pid.Sus.Anak/2016 /PN. DPS, the coercion of criminal sanctions is not applied, but the implementation of Diversion lead on number 11 of 2012 concerning juvenile justyce sistem and in paragraph (2) letters a and b must be sought for Diversion, with terms and conditions Parents are willing to maintain, guide and supervise their children so that they will not repeat their actions.